The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1029/2022av000729
|View full text |Cite
|
Sign up to set email alerts
|

Lower Urban Humidity Moderates Outdoor Heat Stress

Abstract: Surface temperature is often used to examine heat exposure in multi‐city studies and for informing urban heat mitigation efforts due to scarcity of urban air temperature measurements. Cities also have lower relative humidity, traditionally not accounted for in large‐scale observational urban heat risk assessments. Here, using crowdsourced measurements from over 40,000 weather stations in ≈600 urban clusters in Europe, we show the moderating effect of this urbanization‐induced humidity reduction on outdoor heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 85 publications
4
30
0
Order By: Relevance
“…Moreover, it is also one of the first to use these methods to predict the spatial variability of RH, and thus estimates of ambient moist heat stress. We find that, when combined with other ancillary information, satellite-derived LST can be a strong predictor of ambient air temperature, even though using LST directly as a proxy for urban heat exposure may be misleading (Chakraborty et al 2022, Turner et al 2022. Overall, since our ML model identified LST from both the Landsat two-month average and the closest time period as being the variables contributing the most predictive power to our model, this means that the air temperature variability is embedded within LST variability, as reflected in the feature importance scores (figure 2).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, it is also one of the first to use these methods to predict the spatial variability of RH, and thus estimates of ambient moist heat stress. We find that, when combined with other ancillary information, satellite-derived LST can be a strong predictor of ambient air temperature, even though using LST directly as a proxy for urban heat exposure may be misleading (Chakraborty et al 2022, Turner et al 2022. Overall, since our ML model identified LST from both the Landsat two-month average and the closest time period as being the variables contributing the most predictive power to our model, this means that the air temperature variability is embedded within LST variability, as reflected in the feature importance scores (figure 2).…”
Section: Discussionmentioning
confidence: 90%
“…Studies have found positive correlation between satellite-derived LST and air temperature (Mildrexler et al 2011, Zhang et al 2014, particularly during nighttime (Chakraborty et al 2022), and LST data have been widely used as a proxy for urban heat exposure in the past (Chakraborty et al 2019, Manoli et al 2019, Hoffman et al 2020, Hsu et al 2021, McDonald et al 2021, Mentaschi et al 2022. In this study, the LST data from satellite sensors Landsat 8 and MODIS were examined, since both data sources have their advantages and trade-offs.…”
Section: Landsat Lst Datamentioning
confidence: 96%
“…Hence, fine-scale LST observations can still provide valuable insights into intracity temperature gradients and complexities at detailed levels that are difficult to achieve with meteorological temperature data alone. Moving forward, more urban-scale in situ observations of air temperature and other relevant meteorological variables are urgently needed to better understand urban heat exposure ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, different data processing techniques applied to this study compared to the previous studies might have resulted in different outcomes. t is challenging to explain heat measures' relationship with the individual variable comparison results directly since the effect of RH on HI is nonlinear according to Ta increase, and WBGT is the weighted sum of natural wet bulb temperature, black globe temperature, and air temperature (Chakraborty et al, 2022).…”
Section: Discussionmentioning
confidence: 99%